Precursor‐Directed Diversification of Cyclic Tetrapeptidic Pseudoxylallemycins. (4th October 2018) - Guo, Huijuan; Schmidt, Alexander; Stephan, Philipp; Raguž, Luka; Braga, Daniel; Kaiser, Marcel; Dahse, Hans‐Martin; Weigel, Christiane; Lackner, Gerald; Beemelmanns, Christine
Abstract: Cyclic peptides containing non‐proteinogenic amino acids often exhibit a broad bioactivity spectrum and many have entered clinical trials with good prospects for drug development. We recently reported the discovery of six cyclic tetrapeptides, pseudoxylallemycins A–F (1 –6 ), from a termite‐associated Pseudoxylaria sp. X802. These compounds contain a rare O ‐homoallenyl‐l ‐tyrosine moiety and show promising antimicrobial activity against the Gram‐negative pathogenic bacterium Pseudomonas aeruginosa . To perform more detailed structure–activity studies, we pursued a precursor‐directed diversification strategy. Herein, we report the purification, identification, and testing of 21 new pseudoxylallemycin derivatives. Abstract : Pep talk : Cyclic peptides containing non‐proteinogenic amino acids often exhibit a broad bioactivity spectrum and many have entered clinical trials with good prospects for drug development. Herein, 21 new cyclic pseudoxylallemycin tetrapeptides are identified; their antimicrobial activities are assessed, and first studies towards their chemical derivatization are performed.